Formation of the Virtual Educational Environment of the University in the Conditions of Education Informatization - Lyudmila PET’KO; Vanda VYSHKIVSKA; Liudmyla OVSIIENKO; Olena KULYK; Oleksandra SHYKYRYNSKA (Communications of International Proceedings, 2020)
The introduction of the unified technology platform for the deployment of the cloud-based educational environment in higher education institution helps to solve numerous problems of unifying the architecture of the environment, integrating the technological infrastructure of learning on a single basis, providing wider access to better samples of electronic resources and services. When designing a cloud-oriented learning environment, it is advisable to use a hybrid service model of its structure, its content covers electronic resources of educational and scientific purpose. The holistic model of specialist training in the cloud-oriented environment contains levels and components of competence that are inherent for the process of training scientific and pedagogical staff of the education informatization trained in a high-tech environment. The integration of different subsystems of the environment into a single training system ensures the integrity of this process through the separation of invariant factors inherent in different branches of education.
Keywords: Holistic Model; Electronic Resource; Environment Architecture; Hybrid Service Model; Educational Informatization.